2013
DOI: 10.1007/s00224-013-9459-y
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Anarchy in Network Creation Games Is (Mostly) Constant

Abstract: Abstract. We study the price of anarchy and the structure of equilibria in network creation games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 14 publications
7
54
0
Order By: Relevance
“…First, we prove that computing a best response for a player is NP-hard for any 0 < α = o(n), thus extending a similar result given in [13] for MaxNCG when α = 2/n. Then, we prove that MaxNCG(H) is not a potential game, by showing that an improving response dynamic does not guarantee to converge to an equilibrium, even if we assume a minimal liveness property that no player is prevented from moving for arbitrarily many steps.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…First, we prove that computing a best response for a player is NP-hard for any 0 < α = o(n), thus extending a similar result given in [13] for MaxNCG when α = 2/n. Then, we prove that MaxNCG(H) is not a potential game, by showing that an improving response dynamic does not guarantee to converge to an equilibrium, even if we assume a minimal liveness property that no player is prevented from moving for arbitrarily many steps.…”
Section: Introductionsupporting
confidence: 61%
“…Consequently, the Nash Equilibria 1 (NE) space of the game is a function of it. Actually, if we characterize such a space in terms of the Price of Anarchy (PoA), then this has been shown to be constant for all values of α except for n 1−ε ≤ α ≤ 65 n, for any ε ≥ 1/ log n (see [12,13]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors show that the price of anarchy is constant for α ≤ √ n and for α ≥ 12n log n. In the latter case they prove that any pure equilibrium is a tree. This bound was improved in [30], where it was shown that for α ≥ 273n all pure equilibria are trees. Later on, in [27], this was further improved by showing that it even holds for α ≥ 65n.…”
Section: Related Literaturementioning
confidence: 99%
“…The paper [13] introduces a version of the game where the distance cost of a player is defined the maximum distance from i to any other player (instead of the sum of distances), and studies the price of anarchy for these games. Further results on those games can be found in [30]. Another natural variant of a cost sharing game is one where both endpoints of an edge can contribute to its creation, as proposed in [29], or must share its creation cost equally as proposed in [12] and further investigated in [13].…”
Section: Related Literaturementioning
confidence: 99%